COPD and Cardiovascular Disease - André, S (2019)
COPD is one of the major public health problems in people aged 40 years or above. It is currently the 4th leading cause of death in the world and projected to be the 3rd leading cause of death by 2020. COPD and cardiac comorbidities are frequently associated. They share common risk factors, pathophysiological processes, signs and symptoms, and act synergistically as negative prognostic factors. Cardiac disease includes a broad spectrum of entities with distinct pathophysiology, treatment and prognosis. From an epidemiological point of view, patients with COPD are particularly vulnerable to cardiac disease. Indeed, mortality due to cardiac disease in patients with moderate COPD is higher than mortality related to respiratory failure. Guidelines reinforce that the control of comorbidities in COPD has a clear benefit over the potential risk associated with the majority of the drugs utilized. On the other hand, the true survival benefits of aggressive treatment of cardiac disease and COPD in patients with both conditions have still not been clarified. Given their relevance in terms of prevalence and prognosis, we will focus in this paper on the management of COPD patients with ischemic coronary disease, heart failure and dysrhythmia.